2021
DOI: 10.1055/s-0041-1726424
|View full text |Cite
|
Sign up to set email alerts
|

Cysto-Vaginoscopy of a 3D-Printed Cloaca Model: A Step toward Personalized Noninvasive Preoperative Assessment in Patients with Complex Anorectal Malformations

Abstract: Introduction For the classification of the complexity of cloacal malformations and the decision on the operative approach, an exact anatomical assessment is mandatory. To benefit from using three-dimensional (3D)-printed models in preoperative planning and training, the practicability of these models should be guaranteed. The aim of this study was to evaluate the quality and feasibility of a real-size 3D-printed cloaca model for the purpose of cysto-vaginoscopic evaluation. Materials and Methods We p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Hp infection is an important trigger of chronic gastritis and peptic ulcer, and research data show that some immune mechanisms and inflammatory responses play an important role in the pathogenesis of gastric mucosa, and nowadays, diseases due to cytokine triggers are getting more and more attention [ 14 ]. Hp-positive chronic gastritis and peptic ulcer make some cells in patients to form an immune response, in which endocrine secretion of serum IL-6, IL-8, and TNF- α and other cytokines is endocrine raised [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hp infection is an important trigger of chronic gastritis and peptic ulcer, and research data show that some immune mechanisms and inflammatory responses play an important role in the pathogenesis of gastric mucosa, and nowadays, diseases due to cytokine triggers are getting more and more attention [ 14 ]. Hp-positive chronic gastritis and peptic ulcer make some cells in patients to form an immune response, in which endocrine secretion of serum IL-6, IL-8, and TNF- α and other cytokines is endocrine raised [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of endometrial polyps is the rapid proliferation of the basal endothelium, and the diameter of polyps is usually 0.5-2.0 cm. Traditionally, patients are examined for endometrial polyps by using the transvaginoscopy method, which depicts the general condition of the object based on the reflection of the detected object to ultrasound waves [16]. However, some studies have shown that although transvaginoscopy has a high positive value for Patient satisfaction data in this study were entered into excel software by the first author and corresponding author, respectively, and count data were described as whole numbers, and included data were tested for compliance with normal distribution using the Shapiro-Wilk method; count data were described as whole numbers, and the χ2 test was used between or within groups.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of endometrial polyps is the rapid proliferation of the basal endothelium, and the diameter of polyps is usually 0.5-2.0 cm. Traditionally, patients are examined for endometrial polyps by using the transvaginoscopy method, which depicts the general condition of the object based on the reflection of the detected object to ultrasound waves [ 16 ]. However, some studies have shown that although transvaginoscopy has a high positive value for diagnosing endometrial polyps, it is difficult to diagnose polyps with a diameter of less than 0.5 cm, and the diagnostic value of multiple polyps is not high.…”
Section: Discussionmentioning
confidence: 99%
“…• Di cult to simulate an ARM in an animal patient -derived intestinal organoid epithelium in a physiodynamic mucosal interface on a chip has been developed [9] The multiaxial deformations in a convoluted microchannel not only induced dynamic cell strains but also enhanced particle mixing in the lumen microchannel [9]. 3D reconstructions have been used in surgical training to understand the anatomy, provide a simulated operative pro le simulation of cysto-vaginoscopy for training [10]. Evaluation of the quality and feasibility of a real-size 3D printed cloacal model for cysto-vaginoscopic evaluation as a valuable add-on tool for specialty training in pediatric colorectal surgery was done by Krois et al [10].…”
Section: Resultsmentioning
confidence: 99%